Cost Control of EPC Project of Water Conservancy Project under FIDIC Framework - Lin, Jinquan (Journal of Progress in Civil Engineering, 2025)
With the deep integration and development of the international engineering contracting market, the number of EPC projects of water conservancy projects using FIDIC 'design-procurement-construction (EPC) / turn-key project contract conditions' (silver book) is increasing. The design-procurement-construction (EPC) general contracting model has been widely used in large-scale water conservancy projects because of its advantages of effectively integrating resources, clarifying the main body of responsibility, and shortening the construction period. The International Federation of Consulting Engineers (FIDIC) issued the "Design Procurement Construction (EPC)/ Turnkey Project Contract Conditions" (commonly known as the "Silver Book") [1], which is a model contract for international EPC projects. Because the silver book stipulates the principle of risk allocation, the contractor needs to have high cost control ability. The purpose of this paper is to deeply study the dynamic and systematic cost control strategy covering the whole process of bidding quotation, design, procurement, construction and contract management under the framework of FIDIC silver book, so as to improve the international project management level and profitability of Chinese contractors.